2018
DOI: 10.1038/s41598-018-32836-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the association of EPHB6, EFNB1 and EFNB3 variants with hypertension risks in males with hypogonadism

Abstract: Several members of the EPH kinase family and their ligands are involved in blood pressure regulation, and such regulation is often sex- or sex hormone-dependent, based on animal and human genetic studies. EPHB6 gene knockout (KO) in mice leads to hypertension in castrated males but not in un-manipulated KO males or females. To assess whether this finding in mice is relevant to human hypertension, we conducted a human genetic study for the association of EPHB6 and its two ligands, EFNB1 and EFNB3, with hyperten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…In all such cases, sex hormones act in concert with these EPHs/EFNs to control BP. Some of the findings from the mouse model have been corroborated by human genetic studies, in which we revealed that some variants in the EFNB2, EFNB3, and EPHA4 genes or a related signaling molecule gene are significantly associated with hypertension in a sex-specific way (19,21,22,24,25).…”
supporting
confidence: 58%
See 1 more Smart Citation
“…In all such cases, sex hormones act in concert with these EPHs/EFNs to control BP. Some of the findings from the mouse model have been corroborated by human genetic studies, in which we revealed that some variants in the EFNB2, EFNB3, and EPHA4 genes or a related signaling molecule gene are significantly associated with hypertension in a sex-specific way (19,21,22,24,25).…”
supporting
confidence: 58%
“…In all such cases, sex hormones act in concert with these EPHs/EFNs to control BP. Some of the findings from the mouse model have been corroborated by human genetic studies, in which we revealed that some variants in the EFNB2, EFNB3, and EPHA4 genes or a related signaling molecule gene are significantly associated with hypertension in a sex-specific way (19,21,22,24,25).EPHB6 is highly expressed in the medullae of adrenal glands, which are the major source of catecholamine (CAT) in the circulation. The ambient blood CAT level reflects this hormone's effect on the homeostasis of BP (26,27).…”
mentioning
confidence: 59%
“…CCL20 [188], CRH (corticotropin releasing hormone) [189], SPP1 [190], LDLR (low density lipoprotein receptor) [191], RORA (RAR related orphan receptor A) [192], LYZ (lysozyme) [193], PTPRN2 [194], DAPK2 [195], OIP5 [196], PON3 [197], NR4A3 [198], VCAN (versican) [199], CNTNAP2 [200], IL1RAP [201], GLI2 [202], CDH13 [203], AEBP1 [204], BGN (biglycan) [205], LOX (lysyl oxidase) [206], IL1RL1 [207] and LUM (lumican) [208] were found to be involved in advancement of obesity, but these genes might be key for development of T2DM. C4BPA [209], KYNU (kynureninase) [210], ORM1 [211], ARSA (arylsulfatase A) [212], CYB5R3 [213], MAT1A [214], SDC4 [215], ASL (argininosuccinate lyase) [216], SLC4A4 [217], EPHB6 [218], SPARCL1 [219], THBS2 [220], EFNB2 [221] and CD248 [222] were revealed to be associated with hypertension, but these genes might be involved in progression of T2DM. GSDMD (gasdermin D) [223], UNC5B [224] and PDGFB (platelet derived growth factor subunit B) [225] have been reported significantly expressed in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the patient population were previously described (Wu et al, 2018) but are presented here again for the convenience of readers. A total of 4,480 male patients ≥40 years old from the Cardiology Ward, Endocrinology Ward, and Physical Examination Center of First Affiliated Hospital, College of Medicine, Zhejiang University in Hangzhou, China, were recruited for this study.…”
Section: Patient Populationmentioning
confidence: 99%